Public Governance Quality and Tax Compli ance Behavior in Nigeria: The Moderating Role of Financial Condition and Risk Preference (Issues in Social and Environmental Accounting (ISEA), 2011)
To have better understanding of compliance behavior of individual taxpayers in developing countries especially Nigeria, this study is undertaken primarily to test relationship between taxpayers’ perception about public governance quality and their compliance behavior as well as to determine whether the relationship is moderated by financial condition and risk preference individually and jointly. This study involved a survey of individual taxpayers’ opinion, perception and behavior about public governance quality as well as tax compliance. The major finding of this study is that public governance quality has significant positive relationship with tax compliance behavior. The study also indicates that risk preference has strong negative moderating effect on the relationship between public governance quality and tax compliance behavior. Administration of income tax in Nigeria is characterized by low compliance level and therefore, there is no doubt that improvement in public governance quality would contribute significantly in reawakening the culture of tax compliance among individual taxpayers in Nigeria. Empirically, nothing much is known in tax compliance literature about the influence of public governance quality on tax compliance behavior of individual taxpayers as well as the moderating effect of financial condition and risk preference on tax compliance and its determinants. This study extended tax compliance model to incorporate public governance quality and moderating effects of financial condition and risk preference.